2021
DOI: 10.1155/2021/7805617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bedding Geometry and Cementation Strength on Shale Tensile Strength Based on Discrete Element Method

Abstract: To study the effects of anisotropy and heterogeneity on the shale failure mode and tensile strength, Brazilian splitting tests were performed from both directions of the bedding and layer thickness. Layers containing different bedding and loading angles and layer thicknesses were obtained separately. The results show that, at 0° and 90° angles, the shale cracks grow “linearly”; at 15°, the shale cracks have “arc type” growth; and at 30°–75°, the shale-splitting displays “broken line” crack propagation. The ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to the description in the literature, the failure characteristics of the disc after splitting are explained by the stress field distribution during the experiment loading process, and the theory is used to verify the adequacy and correctness of the above analysis. As shown in Figure a,b, a homogeneous shale disc model without Lamina was created in 3DEC discrete element simulation software, which was used to load and record the nondimensional vertical stress field distribution characteristics of the disc and the loading nephogram of the homogeneous model, the nondimensional horizontal stress field distribution characteristics, and the load–displacement nephogram of the homogeneous model.…”
Section: Results and Analysismentioning
confidence: 99%
“…According to the description in the literature, the failure characteristics of the disc after splitting are explained by the stress field distribution during the experiment loading process, and the theory is used to verify the adequacy and correctness of the above analysis. As shown in Figure a,b, a homogeneous shale disc model without Lamina was created in 3DEC discrete element simulation software, which was used to load and record the nondimensional vertical stress field distribution characteristics of the disc and the loading nephogram of the homogeneous model, the nondimensional horizontal stress field distribution characteristics, and the load–displacement nephogram of the homogeneous model.…”
Section: Results and Analysismentioning
confidence: 99%
“…To some content, the numerical methods are competent to understand the effects of rock heterogeneity on the rock mechanical properties and fracture properties, which could also overcome the experimental uncertainly, especially from a micro-level . Currently, numerical simulation studies on shale anisotropy mainly focus on the effect of weak bedding, these studies have greatly deepened the understanding of the mechanical characteristics of shale anisotropy. For example, Wang et al found that the stratified rock discs showed obvious directionality in the tensile strength, which is manifested by the variation of strength with bedding orientation.…”
Section: Introductionmentioning
confidence: 99%